GROWTH RESPONSE OF Cattleya sp. ORCHIDS AFTER ACCLIMATIZATION ON THE GIVING OF VARIOUS CONCENTRATION OF LIQUID ORGANIC FERTILIZER - Novianti, Evi (Jurnal Sains Pertanian Equator, 2019)
The proper concentration of fertilizers is needed to getting the optimal growing of orchid seeds. This study aims to determinate the best concentration of liquid organic fertilizer on the growth of Cattleya sp. after acclimatization. The reseach was conducted at the reseach house of Agriculture Faculty of Tanjungpura University, start from October 28th, 2017 to February 12nd, 2018. This study used an experimental method with a Complete Randomized Design pattern (CRD). The treatment consists of 5 levels concentration of Bio Sugih liquid organic fertilizer that is: p1= 0,5 ml/l, p2= 1,0 ml/l, p3= 1,5 ml/l, p4= 2,0 ml/l and p5= 2,5 ml/l with 5 replication consisting of 4 sample plants. Variables observed in this study is: increase in the amount of leaves (strands), increase of leaf length (cm), increase of leaf width (cm), increase in the amount of roots (strands), increase of root length (cm) and amount of tillers per plant. The research results showed that aplication of liquid organic fertilizer at various concentration gave a good growth response on the length and width of Cattleya leaf after acclimatization. The effective concentration of liquid organic fertilizer for the growth of Cattleya sp. is 0,5 ml/l.